The Term of Office of The President of The Syrian Arab RepublicAnd How it Ends According to The 2012 Constitution (Damascus University Journal for the economic and Political sciences, 2024)
The President of the Syrian Arab Republic occupies a critical importance in the political life of the country, as he exercises truly broad powers, including the power to appoint, defend, preside over the Council of Ministers, and direct public policy ... In clearer terms, the President plays a pivotal role in the Syrian constitutional system, He is the head of state, the head of the executive authority, and he protects the interests of the people and their freedoms, preserves the sovereignty, independence, and freedom of the country, defends the integrity of its lands, protects the constitution, the regular functioning of public authorities, the protection of national unity and the survival of the state, and exercises these enormous powers for a term of insult New Years. Therefore, all of its vacancies will have repercussions and repercussions for the stability of the state and its constitutional institutions. In view of the importance of the powers of the President of the Syrian Arab Republic, the constitutional legislator has decided on constitutional provisions that control the vacancies of the position of the President of the Republic, whether it is the end of his term in a regular or non-greedy (premature) manner, such as death or resignation, temporary or permanent impediment, or a case where the President of the Republic is accused of high treason that Create temporary vacancy during the period of indictment.
Keywords: Term Of Office Of The President Of The Syrian Arab Republic; The Ordinary And Extraordinary End Of The Term Of Office Of The President Of The Republic; The Parliamentary Political Procedures Related To The Election Of The President Of The Republic